Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1108/nfs-06-2014-0053
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characterisation of thickened fluids under different temperature, pH and fat contents

Abstract: Purpose – The purpose of this paper was to examine the rheological characterisation of thickened water under different temperature and pH conditions and thickened milk with different fat contents. Design/methodology/approach – Beverages thickened with powdered thickeners are used in the medical management of individuals who suffer swallowing difficulties (dysphagia). Each individual requires a specific level of thickness to best meet the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 28 publications
(52 reference statements)
0
17
2
Order By: Relevance
“…Viscosity is only one of a number of relevant parameters affecting liquid flow; others include density, yield stress, sample temperature, elasticity, and propulsion pressure [6569]. …”
Section: Discussionmentioning
confidence: 99%
“…Viscosity is only one of a number of relevant parameters affecting liquid flow; others include density, yield stress, sample temperature, elasticity, and propulsion pressure [6569]. …”
Section: Discussionmentioning
confidence: 99%
“…The variations observed suggest some instability in the product for reasons that are unknown. However, recent studies have shown that the viscosity of milk products varies based on protein and fat content [16, 17]. Given fact that the Enfamil AR™ specialty formulas involve elements designed to reduce acid reflux and/or provide caloric fortification, it is tempting to speculate that protein or fat content may be contributing to increased viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the heavy dependence of the viscosity of thickened fluids on a number of factors. These include: differences in thickening agent (Sopade et al, 2007(Sopade et al, , 2008aGarcia et al, 2005), solids content of the liquid (Sopade et al, 2008a), and differences in dispersing medium (Sopade et al, 2007;Garcia et al, 2005;Nicholson et al, 2008) Previous work has focused on investigating the rheological properties of thickened milk and other dispersing media (Hadde et al, 2015;Sopade et al, 2008a). Thickened milk is a fluid that is commonly served to patients, as it offers fluids for hydration in addition to much needed protein and calcium (Claes et al, 2012;Barr et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…The role of fat in the thickened milk has previously been studied and reported. It was reported that fat increases the equilibrium viscosity of thickened milk (Hadde et al, 2015). The objective of the current study was to:…”
Section: Introductionmentioning
confidence: 99%